Selected risk factors for adverse events in hospitalised patients in healthcare facilities - Sowińska, Izabela M.; Noppenberg, Mirosława; Gniadek, Agnieszka (Nursing Problems / Problemy Pielęgniarstwa, 2024)
Recently, adverse events have been a key focus of research. They are an indispensable element of the quality of services provided in healthcare entities. Interest in the issue has increased due to the crucial importance of patients’ safety. Due to the actions of various determining factors, patients staying in medical institutions are at risk of adverse events. The phenomenon of adverse events is not fully known in Poland, due to the lack of a uniform system for their reporting and recording. The Council of Europe on 9 June 2009 issued recommendations on patient safety, including the prevention and control of healthcare-associated infections, which clearly state that adverse event monitoring systems should be set up and analysed in European Union (EU) member states to obtain full information on the extent and causes of incidents. In order to improve patient safety in the health system, the European Council recommends a standardised system for monitoring and reporting of adverse events. An analysis of the literature shows that adverse events have a wide variety of risk factors. This gives grounds to conclude that the topic of risk factors for such events is a very broad one. The results of available studies show risk factors on the part of those providing direct patient care, e.g. error on the part of the person performing the procedure or activity, error on the part of those providing indirect patient care, including organisational, management, and system errors, as well as external factors relating to the medical equipment used for patient care, as well as the key risk factors relating to patients themselves. The latter are the subject of the analysis undertaken. The aim of this report is to present selected risk factors for adverse events among inpatients in medical facilities.